Clinical presentation of 54 patients with endogenous hyperinsulinaemic hypoglycaemia: a neurological chameleon (observational study) (Swiss Medical Weekly, 2018)
BACKGROUND Important causes of endogenous hyperinsulinaemic hypoglycaemia (EHH) in adult patients are insulinoma and adult nesidioblastosis. Data on main symptoms in EHH are scarce and controversial. We analysed main symptoms of patients with EHH in the framework of two prospective studies investigating glucagon-like peptide-1 receptor imaging. METHODS Patients were referred from secondary European endocrine centres and endocrinologists. Inclusion criteria were biochemically proven EHH (glucose